Observations of the Antarctic Slope Current in the Southeastern Weddell Sea: A Bottom-Enhanced Current and Its Seasonal Variability - Darelius, Elin; Fer, Ilker; Janout, Markus; Daae, Kjersti; Steiger, Nadine (Journal of Geophysical Research: Oceans, 2024)
Abstract The Antarctic Slope Front and the associated Antarctic Slope Current dynamically regulate the exchanges of heat across the continental shelf break around Antarctica. Where the front is weak, relatively warm deep waters reach the ice shelf cavities, contributing to basal melting and ultimately affecting sea level rise. Here, we present new 2017?2021 records from two moorings deployed on the upper continental slope (530 and 738 m depth) just upstream of the Filchner Trough in the southeastern Weddell Sea. The structure and seasonal variability of the frontal system in this region, central to the inflow of warm water toward the large Filchner-Ronne Ice Shelf, is previously undescribed. We use the records to describe the mean state and the seasonal variability of the regional hydrography and the southern part of the Antarctic Slope Current. We find that (a) the current is, contrary to previous assumptions, bottom-enhanced, (b) the isotherms slope upwards toward the shelf break, and more so for warmer isotherms, and (c) the monthly mean thermocline depth is shallowest in February-March and deepest in May-June while (d) the current is strongest in April-June. On monthly timescales, we show that (e) positive temperature anomalies of the de-seasoned records are associated with weaker-than-average currents. We propose that the upward-sloping isotherms are linked to the local topography and conservation of potential vorticity. Our results contribute to the understanding of how warm ocean waters propagate southward and potentially affect basal melt rates at the Filchner-Ronne Ice Shelf.
Publisher: John Wiley & Sons, Ltd Article number: e2023JC020666
Keywords: Sørishavet; Weddellhavet; havstrømmer; oseanografi

Combined physical and biogeochemical assessment of mesoscale eddy parameterisations in ocean models: Eddy-induced advection at eddy-permitting resolutions - Ruan, X.; Couespel, D.; Lévy, M.; Li, J.; Mak, J.; Wang, Y. (Ocean Modelling, 2024)
Ocean general circulation models at the eddy-permitting regime are known to under-resolve the mesoscale eddy activity and associated eddy-mean interaction. Under-resolving the mesoscale eddy field has consequences for the resulting mean state, affecting the modelled ocean circulation and biogeochemical responses, and impacting the quality of climate projections. There is an ongoing debate on whether and how a parameterisation should be utilised in the eddy-permitting regime. Focusing on the Gent–McWilliams (GM) based parameterisations, it is known that, on the one hand, not utilising a parameterisation leads to insufficient eddy feedback and results in biases. On the other hand, utilising a parameterisation leads to double-counting of the eddy feedback, and introduces other biases. A recently proposed approach, known as splitting, modifies the way GM-based schemes are applied in eddy-permitting regimes, and has been demonstrated to be effective in an idealised Southern Ocean channel model. In this work, we evaluate whether the splitting approach can lead to improvements in the physical and biogeochemical responses in an idealised double gyre model. Compared with a high resolution mesoscale eddy resolving model truth, the use of the GM-based GEOMETRIC parameterisation together with splitting in the eddy-permitting regime leads to broad improvements in the control pre-industrial scenario and an idealised climate change scenario, over models with and models without the GM-based GEOMETRIC parameterisation active. While there are still some deficiencies, particularly in the subtropical region where the transport is too weak and may need momentum re-injection to reduce the biases, the present work provides further evidence in support of using the splitting procedure together with a GM-based parameterisation in ocean general circulation models at eddy-permitting resolutions.
Article number: 102396
Keywords: Sørishavet; havstrømmer; klimaendringer; oseanografi

Swirls and scoops: Ice base melt revealed by multibeam imagery of an Antarctic ice shelf - Wåhlin, Anna; Alley, Karen E.; Begeman, Carolyn; Hegrenæs, Øyvind; Yuan, Xiaohan; Graham, Alastair G. C.; Hogan, Kelly; Davis, Peter E. D.; Dotto, Tiago S.; Eayrs, Clare; Hall, Robert A.; Holland, David M.; et al. (Science Advances, 2024)
Knowledge gaps about how the ocean melts Antarctica's ice shelves, borne from a lack of observations, lead to large uncertainties in sea level predictions. Using high-resolution maps of the underside of Dotson Ice Shelf, West Antarctica, we reveal the imprint that ice shelf basal melting leaves on the ice. Convection and intermittent warm water intrusions form widespread terraced features through slow melting in quiescent areas, while shear-driven turbulence rapidly melts smooth, eroded topographies in outflow areas, as well as enigmatic teardrop-shaped indentations that result from boundary-layer flow rotation. Full-thickness ice fractures, with bases modified by basal melting and convective processes, are observed throughout the area. This new wealth of processes, all active under a single ice shelf, must be considered to accurately predict future Antarctic ice shelf melt. A unique dataset from beneath an Antarctic ice shelf shows a varied icescape created by differential melt mechanisms.
Publisher: American Association for the Advancement of Science Article number: eadn9188
Keywords: Sørishavet; brehylle; havstrømmer; isbrem; oseanografi